Canto dos estádios: comportamento de consumo de torcedores fanáticos de futebol em tempos de crise - Andrade, Samuel Gonzaga de (2022)
One of the great passions of Brazilian society is football. Around here, it is normal for people to dedicate part of their time to follow their favorite time and engage in organized cheering and fan groups that follow games and discuss issues related to the club and the sport. In this scenario, one of the most popular clubs in Brazil is Cruzeiro Esporte Clube. This club, since 2019, for extra-field reasons, has been experiencing the greatest crisis of its century-old existence - a crisis that was driven by low performance on the field (which resulted in an unprecedented relegation to the second division of the Brazilian Championship) and by the pandemic that has raged around the world since the beginning of 2020 - COVID-19. Within that, this study arises from the following question: “What is the impact of the covid-19 pandemic and the financial and sports crisis experienced by Cruzeiro Esporte Clube on the consumption behavior of its fans / fans?”. Thus, the general objective of this research is to understand how the crisis experienced by Cruzeiro Esporte Clube and the covid-19 pandemic affected the consumption behavior of fans / fans of the time. Thus, theoretical references are focused on better understanding the relationship between consumption and culture, consumption subcultures, as well as sports consumption. To carry out this research, a qualitative approach was used and, as a procedure, Netnography with Cruzeiro fans belonging to the Pró-Cruzeiro group and the organized supporters Mafia Azul. In this, this work contained the following netographic stages: (I) Cultural Entrance - In this, the researcher of the present study belongs to the Pró-Cruzeiro and Máfia Azul groups; (II) Data Collection: through online studies in the communities and interviews with some members to complete the material; (III) Data Analysis and Interpretation – For this, categories were identified and, by categories interpreted based on the literature. Thus, it was observed that the majority of fanatical fans increased their level of engagement with the club after the beginning of the crisis. In addition, these followers attracted relationships within the fans, since they originated from their commitment to the club and therefore, they moved away from people who did not have the same behavior and precisely this Pro-Cruzeiro group. The COVID-19 pandemic, on the other hand, had a negative impact on the behavior of fanatics, on the perceived aspects of the stadium, and mainly had a financial impact on the stadiums. However, it is clear that the respondents did not reduce their level of commitment to the club, as they sought alternatives to overcome these losses.